Aplikasi Lembar Kerja Peserta Didik Untuk SMP Kristen Setia Seriti Berbasis Website - Fraditya P.Titing; Solmin Paembonan; Budiawan Sulaeman (Jurnal Publikasi Teknik Informatika, 2024)
The Learner Worksheet application is an important tool to help and facilitate teaching and learning activities and help in evaluating student knowledge given the rapid development of technology (gadgets) today, for this reason, research and development of LKPD applications with the study of Setia Seriti Christian Junior High School. The method used in the research is the Waterfall method. The results of this study found that:. The Website-Based Learner Worksheet Application for Setia Seriti Christian Junior High School was built using the website programming language with the Laravel Framework and designed using UML models which include activity diagrams, sequence diagrams, class diagrams, The application can run as expected by the researcher. This is based on the results of blackbox testing, the application is feasible to use based on the results of testing the feasibility of the application using the usability factor in the form of a questionnaire resulting in a score of 96% so that it falls into the "Very Feasible" category.